2020
DOI: 10.1073/pnas.1916121117
|View full text |Cite
|
Sign up to set email alerts
|

OGT suppresses S6K1-mediated macrophage inflammation and metabolic disturbance

Abstract: Enhanced inflammation is believed to contribute to overnutrition-induced metabolic disturbance. Nutrient flux has also been shown to be essential for immune cell activation. Here, we report an unexpected role of nutrient-sensingO-linked β-N-acetylglucosamine (O-GlcNAc) signaling in suppressing macrophage proinflammatory activation and preventing diet-induced metabolic dysfunction. Overnutrition stimulates an increase inO-GlcNAc signaling in macrophages.O-GlcNAc signaling is down-regulated during macrophage pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 86 publications
6
56
0
1
Order By: Relevance
“…For example, another study found that depletion of OGT in the human macrophage cell line THP-1 adversely affected M2 polarization, but M1 genes were upregulated ( 31 ). OGT also inhibits the pro-inflammatory activation of macrophages by suppressing the phosphorylation of S6 kinase β-1, suppressing mTORC1 signaling, which prevents pro-inflammatory gene transcription ( 32 ). O-GlcNAcylation is therefore shown to be an essential regulator of macrophage function, affecting both the initial inflammatory response of M1 macrophages and the anti-inflammatory response of M2 macrophages.…”
Section: O-glcnacylation Promotes Opposing Effects In Macrophagesmentioning
confidence: 99%
“…For example, another study found that depletion of OGT in the human macrophage cell line THP-1 adversely affected M2 polarization, but M1 genes were upregulated ( 31 ). OGT also inhibits the pro-inflammatory activation of macrophages by suppressing the phosphorylation of S6 kinase β-1, suppressing mTORC1 signaling, which prevents pro-inflammatory gene transcription ( 32 ). O-GlcNAcylation is therefore shown to be an essential regulator of macrophage function, affecting both the initial inflammatory response of M1 macrophages and the anti-inflammatory response of M2 macrophages.…”
Section: O-glcnacylation Promotes Opposing Effects In Macrophagesmentioning
confidence: 99%
“…Discoveries indicated that S6K1 inhibitors with bevacizumab (anti-VEGF antibody) had potential to modulate the immune response against HCC and immunotherapy methods for HCC [30,31]. O-GlcNAc transferase (OGT) regulated macrophage in ammation by suppressing S6K1 phosphorylation [32]. In addition, IL-2, IL-4, IFN-γ or TNF-α, in tumor B lymphoid cells, could up-regulate S6K1 signaling to enhance cell viability stimulated by B-cell activating factor of the TNF family (BAFF) [33].…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses of liver-specific Ogt knockout mice identified phenotypes including hepatomegaly, fibrosis, inflammation, and necroptosis (Zhang et al, 2019). Ogt floxed mice with LyzM-Cre exhibited metabolic and inflammatory phenotypes compared to Ogt floxed mice without LyzM-Cre (Li et al, 2019;Yang et al, 2020b). Macrophages from these mice exhibit increased proinflammatory responses to bacterial endotoxin LPS (Hasanain Al-Mukh et al, 2020).…”
Section: Investigation Of the Function Of O-glcnacylatedmentioning
confidence: 96%